Dampak Pemekaran Wilayah Terhadap Kinerja Pengembangan Ekonomi - Baban Sobandi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
The establishment of new regional government is intended to improve the peoples welfare in that region. However, it should be noted that this establishment should cosider the gap between the urban and rural areas. It is believed that the establishment will widen the gap since the mobilization of all regional potentials to improve welfare is hindered by this regional differences. The effort to increase the economic growth of the regions can be carried out by optimizing the core potentials, and inviting investor to increase the regional revenues.